2013
DOI: 10.1212/wnl.0b013e3182872694
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of proinflammatory cytokines in patients with Aicardi-Goutières syndrome

Abstract: Objective: This study explores a large panel of cytokines in plasma and CSF of patients with Aicardi-Goutières syndrome (AGS) at different ages, in order to establish signatures of cytokines most predictive of AGS.Methods: Plasma from 22 subjects with known mutations were assayed for cytokines using the Milliplex MAP Immunobead system, and compared to results from 8 age-matched normal controls. CSF of 11 additional patients with mutation-proven AGS was tested in an identical manner and compared to results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
5
13
0
Order By: Relevance
“…Even though IFN-a is considered to be a key biomarker for AGS, the chemokine CXCL10 has also been persistently demonstrated to have an elevated expression in AGS patients (12,13). Consistent with this, our study shows that silencing AGS genes results in an increased expression and release of CXCL10 mainly in astrocytes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Even though IFN-a is considered to be a key biomarker for AGS, the chemokine CXCL10 has also been persistently demonstrated to have an elevated expression in AGS patients (12,13). Consistent with this, our study shows that silencing AGS genes results in an increased expression and release of CXCL10 mainly in astrocytes.…”
Section: Discussionsupporting
confidence: 87%
“…AGS patients also present elevated CSF levels of FMS-related tyrosine kinase 3 ligand, IL-12p40, IL-15, TNF-a, and soluble IL-2 receptor (13). Interestingly, whereas most cytokines decrease exponentially with age in the CSF of patients, CXCL10 levels are persistently elevated beyond early childhood (13). Similar observations have been described for IFN-stimulated genes (ISGs).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Functional knowledge of the zebrafish specific chemokine cxc46 is relatively poor. However, other CXC chemokine family members are upregulated in response to viral infection in zebrafish larvae (18), and increased expression of chemokines has been reported in AGS (42,43). Increased expression of genes encoding the transcription factors irf1b, irf7, stat1b, and cebpb, as observed in our morphants, has also been recorded following exposure to two viruses in zebrafish infection models (18), and significant upregulation of the human orthologs, STAT1 and IRF7 is seen in AGS (7).…”
Section: Discussionsupporting
confidence: 53%
“…Upregulation of both transcripts was confirmed by RT–qPCR, and ELISA of culture supernatants from all six Rnaseh2b −/− lines demonstrated significantly increased CCL5 and CXCL10 secretion (Fig 3D and E, and Appendix Fig S2B). Notably, these cytokines have previously been implicated in AGS neuroinflammation in humans (van Heteren et al , 2008; Takanohashi et al , 2013; Cuadrado et al , 2015). We therefore concluded that impaired RNase H2 activity in vitro and in vivo results in a similar inflammatory response to that observed in patients with AGS, and like for Trex1 deficiency (Gall et al , 2012) is present in non‐immune cells.…”
Section: Resultsmentioning
confidence: 97%